Evaluation of Accuracy of Preoperative Planning of the Femurofibular Angle in Open-Wedge High Tibial Osteotomy for Mild Medial Knee Osteoarthritis - Wang, Peizhao (Biomed Res Int, 2021)
OBJECTIVE: The purpose of this study was to evaluate the usefulness of preoperative planning of the femurofibular angle (FFA) in medial open-wedge high tibial osteotomy (OWHTO) for mild medial knee osteoarthritis. METHODS: Thirty-two patients (32 knees) with mild medial knee OA were retrospectively reviewed. The patients underwent preoperative planning of the FFA for OWHTO. For preoperative planning, a full-length weight-bearing X-ray photograph of the lower limb was opened within Adobe Photoshop Software, and a targeted corrective mechanical axis line of the lower limb and its intersecting point at the lateral tibial plateau surface was drawn using rectangle selection and filling tools. A frame, which encircled the tibia and fibula, was created around the predicted osteotomy plane and then rotated until the ankle center was on the targeted mechanical axis line. Subsequently, a distal femoral condyle line and a proximal fibula axis line were drawn, and the angle between the two lines was measured and defined as the femurofibular angle (FFA). During biplane OWHTO, the preoperatively determined FFA was used to complete the correction of the mechanical axis. During follow-up, the postoperative mechanical weight-bearing line (WBL) of the lower limb, the mechanical femorotibial angle (mFTA), and the FFA were measured and compared with the preoperatively determined values. RESULTS: The mechanical WBL shifted from a preoperative value of 25.36 ± 5.02% to a postoperative value of 56.19 ± 0.10% from the medial border along the mediolateral width of the tibial plateau, and it was 56.57 ± 0.08% at the final follow-up (P < 0.01). The preoperatively determined value was 56.25%, and no significant difference was found compared with postoperative week-one and final follow-up values (P > 0.05). The mFTA was corrected from a preoperative varus of 4.02 ± 0.63° to a postoperative week-one valgus of 2.37 ± 0.28°, and it had a valgus of 2.48 ± 0.39° at the final follow-up (P < 0.01). No significant difference in the valgus was found compared with the postoperative week-one, final follow-up and preoperatively determined valgus of 2.34 ± 0.26° (P > 0.05). The postoperative week-one and final follow-up FFAs were 90.34 ± 1.53° and 90.33 ± 1.52°, respectively, and no significant difference was found compared with the preoperatively determined value of 90.12 ± 1.72° and the intraoperative setting value of 90.25 ± 1.67° (P > 0.05). All corrected values were within the acceptable range of preoperative planning. CONCLUSION: Preoperative planning of the FFA may be useful in OWHTO for patients with mild medial knee OA. Satisfactory correction of the postoperative targeted mechanical axis line of the lower limb can be obtained.